The Efficiency of VAT Implementation : A Comparative Study of Central and Eastern European Countries in Transition - Jack, William (IMF Working Papers; Working Paper ;, 1996)
This paper presents calculations of the efficiency with which value-added taxes are collected in five transition economies in Central and Eastern Europe. Actual VAT revenues in 1994 are compared with those that would have resulted if the statutory VAT rates had been applied without any revenue leakage. The five countries fall into two broad groups, one exhibiting relatively high collection efficiency, and the other relatively low efficiency. While lack of detailed information on tax rules and consumption patterns makes definitive conclusions difficult, the impact of exemptions is shown to likely strengthen the comparative results.